2014
DOI: 10.1021/pr500756u
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Akt1-Mediated Muscle Hypertrophy in Models of Diet-Induced Obesity and Age-Related Fat Accumulation

Abstract: Akt1 is a serine/threonine kinase that promotes cell growth and survival. Previously, Akt1 activation in a double transgenic (DTG) mouse model fed a high-fat/high-sucrose (HF/HS) diet was found to promote type IIb muscle growth and to lead to a significant reduction in obesity. Here, we have used metabolomics to examine the metabolic perturbations in blood serum and liver and gastrocnemius tissues of the DTG mice. Multivariate statistics highlighted consistent metabolic changes in gastrocnemius muscle followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 32 publications
3
54
0
Order By: Relevance
“…Another target gene, DOCK3, that overexpressed it could regulate PTEN/AKT signaling, thereby regulating muscle hypertrophy and growth and inducing apoptosis (Alexander et al, 2014). chi-miR-324-3p, another key miRNA of profile 16, targeted AKT1, which promoted type IIb muscle growth (Cheng et al, 2015). And AKT1 also promoted load-induced muscle hypertrophy by regulating satellite cell proliferation (Moriya and Miyazaki, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another target gene, DOCK3, that overexpressed it could regulate PTEN/AKT signaling, thereby regulating muscle hypertrophy and growth and inducing apoptosis (Alexander et al, 2014). chi-miR-324-3p, another key miRNA of profile 16, targeted AKT1, which promoted type IIb muscle growth (Cheng et al, 2015). And AKT1 also promoted load-induced muscle hypertrophy by regulating satellite cell proliferation (Moriya and Miyazaki, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that APP feeding might convert the lipid composition of fast fibers to that of slow fibers. The accumulation of DHA-containing PC has positive effects on the prevention of obesity 12 , and the amount of PC 18:0/22:6 was increased in a chronic training-induced model of muscle hypertrophy 4 . Therefore, the increase of PC 18:0/22:6 due to APP feeding suggested that APP has effects on lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…AKT1, a serine threonine protein kinase, is a critical mediator of cell growth and survival. AKT1 transgene activation promotes type IIb fiber hypertrophy and increases glycolysis while reducing fat accumulation 35 , 36 . The up-regulation of AKT1 in PiNN may have a functional link to its leanness.…”
Section: Discussionmentioning
confidence: 99%